Blockchain technology and power asymmetries in Tanzanian agricultural supply chains - Deo Shao; Roselyne Alphonce; Fredrick Ishengoma; Hilda Mwangakala; Frederick Chali; Cesilia Mambile; Abiud Bongole; Hector Mongi; Bernard Julius; Aliko Matola (Scientific African)
This study investigates the role of power relations in agricultural supply chains and their impact on sustainability, market access, and technology adoption. Using the Resource Dependence Theory (RDT), this study explains the influence of power asymmetries between stakeholders, such as large buyers and smallholder farmers, on the diffusion of emerging technologies in the Agricultural Supply Chain (ASC) in Tanzania. A mixed-methods approach was employed, combining field surveys in three regions of Tanzania with a comprehensive literature review. The surveys targeted key groups in the ASC, including smallholder farmers, large-scale farmers, buyers, transporters, and local and national leaders. Quantitative data were analysed using descriptive statistics and correlation analyses. The findings show that buyers exert disproportionate influence over pricing (mean score: 5.61), while smallholders, youth, and women remain marginalised (mean scores below 4.0). Large-scale farmers and buyers heavily influence pricing decisions and technology adoption. Correlation analysis reveals a significant disparity, with smallholders and buyers exhibiting almost no pricing alignment (r = 0.002), whereas buyers and national leaders show a close alignment (r = 0.396). Strong AMCOS reported higher stakeholder influence than weak ones (mean 5.76 vs. 4.85). The results signal critical barriers to equitable technology adoption. We argue that blockchain technology can intervene by decentralising information access to rebalance these power asymmetries and enhance market inclusion. The study offers empirical insights for designing inclusive, technology-enabled agricultural markets. The results help policymakers develop targeted interventions to enable smallholders, women, and other disadvantaged groups to access and adopt technologies. Comparative research in different regions could further expand the understanding of how power dynamics and technology adoption evolve.